'Have you ever talked to any women with Turner syndrome?' Using universal design and photo elicitation interviews in research with women with mild cognitive impairment. Issue 2 (May 2019) - Fearon, Kriss
A growing body of methodological research literature demonstrates the importance of adapting research design to address the specific needs of participants from minority groups. The aim is to treat participants more respectfully during the research process and to enhance participation, ensuring the findings more closely reflect participants' views and experience. However, there is an absence of work examining the needs of research participants with Turner syndrome, a chromosome disorder linked with mild cognitive impairment and its potential impact on research interviews. This article draws on a study of reproductive decision-making in women with Turner Syndrome and mothers of girls with Turner syndrome to consider ways to improve research access and to make methodological adaptations for this group of participants. There is little qualitative research on the experience of living with Turner syndrome or its associated experience of infertility. Most of the small number of studies that exist do not describe whether the research method was adapted to accommodate the psychosocial features of Turner syndrome. Yet, these features, which include social cognition issues and anxiety, may have an impact on women's ability to participate fully in a research interview and consequently on the quality of the data. This article fills a gap in research describing the use of adaptions with women with Turner syndrome, which may be of use to researchers and practitioners working with this group. It describes how a novel approach to research adaptations, universal design, was used to identify and incorporate adaptions into the research design, both through the choice of photo elicitation interviews as a research method and through adjustments made at each stage of the research process. It discusses how adaptions worked to overcome barriers to participation and how effective this was, concluding with suggestions for applying this approach in future research.